Prospecção de fungos para o controle de Anticarsia gemmatalis Hübner, 1818 (Lepidoptera: Noctuidae) - Oliveira, Fábio Rodrigo de (2013)
The velvetbean caterpillar, Anticarsia gemmatalis, is considered a major insect pest of soybean. For its control, an alternative to chemical methods is the microbial control, inserted into the pest biological control. Thus, the objective of this study was to isolate fungi from contaminated A. gemmatalis caterpillars and evaluate the pathogenic potential of isolated fungal cultures. For the fungus that caused the greatest mortality percentage of larvae exposed, enzymatic production capacity and production feasibility were found. Still, pathogenicity was evaluated and LC50 and LC90 from the best formulation obtained were established. The fungi isolation occurred from caterpillars on mummification stage, obtained in the central region of Rio Grande do Sul. Larvae mortality, allied to observation of mummification stage, lead to identify the species as Aspergillus nomius presenting the best results (about 95% mortality) among the 20 isolated-fungi. There was no growth of this fungus in culture media rich in chitin and lipids. However, there was growth in a media containing protein, which might suggest that the fungus is a good protease type enzyme producer. Testing to evaluate A. nomius production feasibility, the average spore s concentration (conidia mL-1) in all treatments were similar, with the majority stayed with 1010 conidia.mL-1. Visually, the treatment with 25% water volume per rice volume (50mL), addition of casein in the medium and adding of 6 mL of spore suspension of the fungus A. nomius, which resulted in 2.88 x1010 conidia mL-1, the rice was looser and, therefore, more aired, which may have resulted in a trend toward to a better fungus development. It was evaluated the pathogenicity of this formulated, yielding a high level of mortality among A. gemmatalis larvae, similar to results obtained when spore suspensions originated were applied directly from the fungus growth plates. Yet, at the same conidia concentration mentioned, but testing various dosages, values around 2,23x107 and 1,46x1010 mL.lagarta-1 were obtained, corresponding to LC50 and LC90, respectively, estimated by probit method. Finally, it is concluded that A. nomius presents a high potential regarding to a possible use as A. gemmatalis biological control agent in soybean crops. However, because it is a fungus with pathogenic potential for humans and other native fauna animals, it is necessary further studies related to aflatoxin production by this pathogen and its effects on the environment.